2021
DOI: 10.1007/s15010-021-01726-2
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of SARS-CoV-2 among high-density communities in Saudi Arabia

Abstract: Background The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) infection had been investigated utilizing serology. Materials and methods This community-based sero-survey was carried out in the neighborhoods of three cities in Saudi Arabia. Results Of 5629 participants, 2766 (49.1%) were women; and 2148 (38.1%) were 18–34 years of age, and 3645 (64.7%) were from South East Asia. Positive serology was seen in 2825 (50.2% (95% CI: 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Studies conducted among adult populations reported seroprevalence rates ranging from 1.4% to 50.2%. Other adult studies have also found different seroprevalence values [10,[21][22][23][24]. This study was conducted before the Saudi MoH offered the COVID-19 vaccine for children between 5 and11 years of age, starting in February 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted among adult populations reported seroprevalence rates ranging from 1.4% to 50.2%. Other adult studies have also found different seroprevalence values [10,[21][22][23][24]. This study was conducted before the Saudi MoH offered the COVID-19 vaccine for children between 5 and11 years of age, starting in February 2022.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Although adults in other settings may have been vaccinated before their first SARS-CoV-2 infection, most children have not been. [6][7][8][9] However, both infection then vaccination and vaccination then infection produces broad, hybrid immunity to SARS-CoV-2 with no observed differences by sequence. [32][33][34][35] Our study highlights the differences in SARS-CoV-2 transmission between children and adolescents and adults which may impact transmission dynamics and the transition to endemicity.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Given the high infectivity of SARS-CoV-2 and its emerging variants, many children have already been infected worldwide. [6][7][8][9]. Further, as of June 2022, SARS-CoV-2 vaccine availability and uptake has been limited for children globally.…”
Section: Introductionmentioning
confidence: 99%